Analisis Faktor Penyebab Kecelakaan Lalu Lintas pada Jalan Raya Legundi – Bypass Krian STA 0+000 – STA 5+100 - Abdurrosid Salim; Nugroho Utomo; Achmad Dzulfiqar Alfiansyah (Jurnal Talenta Sipil, 2026)
Traffic accidents remain one of the major transportation problems that continue to increase along with population growth and the rising mobility of the community. This condition leads to a higher risk of traffic accidents, resulting in both material and non-material losses while endangering road users' safety. One of the road sections with a relatively high accident rate is the Legundi–Bypass Krian Road in Sidoarjo Regency, where 23 traffic accident cases were recorded by the Traffic Accident Unit of the Sidoarjo Regional Police in 2024. This study aims to analyze the factors causing traffic accidents, identify accident-prone locations, and evaluate the condition of road safety facilities along the Legundi–Bypass Krian Road. The methods employed include the Accident Equivalent Number (AEN) and the Upper Control Limit (UCL) to identify accident-prone areas (black spots), Importance Performance Analysis (IPA) to analyze accident-causing factors based on road users' perceptions, and a scoring method to assess the feasibility of road safety facilities. The results indicate that human factors are the dominant cause of traffic accidents, several road segments are identified as accident-prone locations based on AEN values exceeding the UCL, and a number of road safety facilities are still in suboptimal condition. Therefore, improving road safety facilities and implementing appropriate treatments at accident-prone locations are recommended to enhance traffic safety.